The impact of consumers’ traveling and media activities on consumer behaviour towards purchasing global brands - Filipović, Jovana; Šapić, Srđan (Hotel and Tourism Management, 2020)
The main objective of this research is an analysis of the impact that consumer travel and the presence of global brands in the media have on the attitudes and intentions which consumers have regarding the purchase of these brands. In order to analyse previously mentioned relationships between the variables, an empirical study was conducted as well as statistical analysis of the obtained data. Testing of hypotheses and relationships between variables was performed using structural equation modelling (SEM). The research results indicate that consumer travel and media activities of global companies have a positive and statistically significant impact on attitudes which consumers have regarding the purchase of global brands, and that attitudes have a very strong and positive impact on consumers’ intentions regarding future purchases of global brands. In addition, it has been found that female consumers, younger and middle-aged consumers, as well as consumers with higher levels of education are more prone to form intentions regarding the purchase of global brands. The study contributes to the existing scientific literature in the field of international marketing and brand management, since there are a certain number of papers in the field of global branding in the foreign scientific literature, while in the domestic scientific literature the mentioned area is relatively unexplored.